Experimental administration of the probiotic Escherichia coli strain Nissle 1917 results in decreased diversity of E. coli strains in pigs - Smajs, David; Bureš, Jan; Smarda, Jan; Chaloupková, Eva; Květina, Jaroslav; Förstl, Miroslav; Kohoutová, Darina; Kuneš, Martin; Rejchrt, Stanislav; Lesná, Jiřina; Kopáčová, Marcela (Current microbiology, 2012)
The strain Escherichia coli Nissle 1917 (EcN) is widely used as an efficient probiotic in therapy and prevention of human infectious diseases, especially of the intestinal system. Concurrently, small adult pigs are being used as experimental omnivore models to study human gastrointestinal functions. EcN bacteria were applied to 6 adult healthy female pigs in a 2-week trial. 6 Control animals remained untreated. Altogether, 164 and 149 bacterial strains were isolated from smear samples taken from gastrointestinal mucosa in the experimental and control group, respectively. Each individual E. coli strain was then tested for the presence of 29 bacteriocin-encoding determinants as well as for DNA markers of A, B1, B2 and D phylogenetic groups. A profound reduction of E. coli genetic variance (from 32 variants to 13 ones, P = 0.0006) was found in the experimental group, accompanied by a lower incidence of bacteriocin producers in the experimental group when compared to control (21.3 and 34.9%, respectively; P = 0.007) and by changes in the incidence of individual bacteriocin types. The experimental administration of EcN strain was not sufficient for stable colonization of porcine gut, but induced significant changes in the enterobacterial microbiota.
Keywords: společenstvo; Molecular Typing; Phylogeny; Genes, Bacterial; Female; střevní sliznice; Escherichia coli; zvířata; Biota; Swine; genetická variace; Genetic Variation; ženské pohlaví; Bacteriocins; fylogeneze; bakteriální geny; molekulární typizace; probiotika; Animals; Intestinal Mucosa; Probiotics; prasata; bakteriociny